2009
DOI: 10.1088/1478-3975/6/4/046010
|View full text |Cite
|
Sign up to set email alerts
|

The cellular response to curvature-induced stress

Abstract: We present a theoretical model to explain recent observations of the orientational response of cells to unidirectional curvature. Experiments show that some cell types when plated on a rigid cylindrical surface tend to reorient their shape and stress fibers along the axis of the cylinder, while others align their stress fibers perpendicular to that axis. Our model focuses on the competition of the shear stress--that results from cell adhesion and active contractility--and the anisotropic bending stiffness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 20 publications
4
57
0
Order By: Relevance
“…Similar observations have been reported in endothelial monolayers where adherens junctions have been shown to be instrumental in this mechanical continuity via the cadherin/catenin complex that can anchor to the stress fibers extremities, independently of the FAs (29). Because of this continuity condition, the theoretical arguments invoking a balance between shear stress and the anisotropic bending stiffness of the stress fibers that were used to describe perpendicular alignment of the stress fibers at the single-cell level may be transposable to the present study (16,18). In this context, the decoration of the individual stress fibers by the FAs that appears to correlate with the circumferential orientation is likely to be an important contribution, as it would limit the impact of the bending anisotropy of the stress fibers themselves that tends to orient the fibers along the wire axis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similar observations have been reported in endothelial monolayers where adherens junctions have been shown to be instrumental in this mechanical continuity via the cadherin/catenin complex that can anchor to the stress fibers extremities, independently of the FAs (29). Because of this continuity condition, the theoretical arguments invoking a balance between shear stress and the anisotropic bending stiffness of the stress fibers that were used to describe perpendicular alignment of the stress fibers at the single-cell level may be transposable to the present study (16,18). In this context, the decoration of the individual stress fibers by the FAs that appears to correlate with the circumferential orientation is likely to be an important contribution, as it would limit the impact of the bending anisotropy of the stress fibers themselves that tends to orient the fibers along the wire axis.…”
Section: Discussionmentioning
confidence: 92%
“…More recently, it has been observed that the response of cells to positive curvature depends strongly on the cell type: Epithelial single cells spread in all directions and favor a circumferential alignment of their actin cytoskeleton (16), while fibroblasts align their cell body and their actin fibers longitudinally (16,17). Some of these differences are captured by a theoretical model in which cell adhesion and active contractility balance the anisotropic bending stiffness of the stress fibers (18). Very recently, monolayers formed from different endothelial cell types cultured on wires were shown to exhibit cell type-dependent orientations (19).…”
mentioning
confidence: 99%
“…For example, active nematic theories predict the influence of substrate curvature on nematic structures . Thus, it will be important to study tissue behavior on out‐of‐plane 2D surfaces that mimic the corrugated surfaces cells encounter in vivo . Another example is the extracellular matrix, which is itself a fibrous material that can exhibit liquid crystalline properties .…”
Section: Resultsmentioning
confidence: 99%
“…For example, the actin network that is the main cytoskeletal component driving morphological changes in the cell can form thick and nematically ordered actin bundles, i.e., stress fibers that anchor adherent cells to the substrate . The active remodeling and anisotropic mechanical properties of the stress fibers and the actin cytoskeleton have been found to influence cell migration and cell chirality, and can lead to the cellular sensing of their microenvironment, such as the sensing of substrate stiffness, substrate curvature, and stretch . For example, the phase transition of the actin network from an isotropic to nematic phase is dependent on the external stress when cells are spreading on soft or stiff substrates, and this contributes to substrate stiffness sensing ( Figure a) .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was found that cells tend to align either parallel or orthogonal to the direction of highest curvature, depending on the cell type. Inspired by these observations mechanical cell models have been proposed that suggest the importance of mechanical stress in the cytoskeleton for the detection of and response to curved structures [27,28].…”
Section: Introductionmentioning
confidence: 99%